A Classification of Features for Interpersonal Disconnectivity in Digital Media: Block, Unfriend, Unfollow, Mute, Withhold, and Eject - Nicholas John (Media and Communication)
This article presents for the first time a classification of, and lexicon for, features for dissolving interpersonal ties in digital environments: blocking, unfriending, unfollowing, muting, withholding, and ejecting. There are two main motivations and two main contributions. The first motivation is that analyses of social media features have not included treatment of features for interpersonal disconnectivity; the second is that analyses of interpersonal disconnectivity have not included reference to the features that enable it. The two main contributions are the disambiguation of a confusing terminological field, thus making it possible to analytically distinguish between types of feature, and an intervention in the question of whether the features described in the article concern filtering information or avoiding people. Data were collected from 37 social media platforms and other services that enable digitally-mediated communication. Features for interpersonal disconnectivity were documented and then the features were grouped based on five questions about their use, where A is the person using the feature, and B is the target of A’s use of the feature: (a) Does it affect A’s feed?; (b) does it affect B’s feed?; (c) is A still connected to B?; (d) is B still connected to A?; (e) can A and B see each other’s profile?